Folic Acid-Decorated Chitosan-PLGA Nanobiopolymers for Targeted Drug Delivery to Acute Lymphoblastic Leukemia Cells: Studies - Fatemeh Ramezani MSc; Maryam Moghadasi MSc; Karim Shamsasenjan PhD; Asghar Narmani PhD (Technology in Cancer Research & Treatment)
Objectives This study developed a drug delivery system (DDS) using folic acid (FA)-functionalized chitosan (CS) and poly (lactic-co-glycolic acid) (PLGA) nanocarriers for targeted sodium butyrate (NB) delivery to leukemia cells (NALM6). The goal was to enhance NB's therapeutic efficacy while reducing its cytotoxicity to non-malignant cells. Methods FA-CS-PLGA nanocarriers were synthesized and characterized using Fourier-transform infrared spectroscopy (FT-IR), dynamic light scattering (DLS), zeta potential analysis, transmission electron microscopy (TEM), and thermogravimetric analysis (TGA). Encapsulation efficiency, release kinetics, cytotoxicity, and apoptosis induction were assessed using MTT assays and flow cytometry in NALM6 cells. Results The FA-CS-PLGA nanocarriers had a surface charge of 34.2 ± 0.12 mV and a size range of 40–60 nm. Encapsulation efficiency was 16%, with 16% of NB released within the first 4 h. MTT assays showed a reduction in leukemia cell viability to 26% after 24 h with 400 nM FA-CS-PLGA-NB, compared to over 50% viability with pure NB. The IC50 was around 300 nM. Flow cytometry revealed that FA-CS-PLGA-NB induced apoptosis in over 20% of leukemia cells, far exceeding the 5% induced by unmodified NB. Conclusion FA-CS-PLGA nanocarriers show significant promise as a targeted DDS for leukemia therapy, enhancing NB delivery to leukemia cells and improving therapeutic efficacy while minimizing off-target toxicity. These results support further in vivo studies and potential clinical applications.